Analisis Masalah Kelembagaan dan Manajerial Koperasi di Indonesia Berdasarkan Studi Literatur - Iwan Mulyana; Tryiis ARR (J-Coop : Journal of Co-operative, 2025)
Cooperatives in Indonesia, as a pillar of the people’s economy, have undergone a long journey from the post-independence era to the digital age. However, the quantitative growth of cooperatives has not been matched by improvements in institutional and managerial quality. This article aims to systematically analyze the institutional and managerial problems of cooperatives in Indonesia based on a literature review from various historical periods: pre-New Order, New Order, and the Reformation to digital era. This research applies a descriptive-qualitative literature review method by examining scholarly journals, books, regulations, and government reports. The key findings reveal chronic issues in cooperatives, including weak organizational structures, unaccountable governance, low human resource capacity, limited member participation, and ineffective regulation and oversight. The digital era further intensifies challenges related to innovation and technology adoption. Institutional reform, improved managerial capacity, active member participation, digital system integration, and regulatory harmonization are essential steps to sustainably strengthen cooperatives.